RTP stream transferring scheme with load balancing and delay optimization in PoC - LIU Hai-peng; LIAO Jian-xin; ZHU Xiao-min (Tongxin xuebao, 2010)
After modeling the RTP（real-time transport protocol） stream transferring scheme proposed by OMA（open mobile alliance） for PoC（push to talk over cellular） server,an improved scheme was presented.Under the new scheme media traffic through CS（controlling server） could be reduced largely and the transferring delay of RTP package could also be shortened obviously by enhancing PS（participating server） controlling capabilities and importing distrib-uted-controlling ideas into PoC system.Analyzing and simulation results show that the new scheme always performs bet-ter than the original one in fields of load balancing and media transferring delay optimization.